Small mammals in owl pellets from the Arid Chaco of Córdoba province (Argentina), including the first records of Microcavia jayat (Rodentia, Caviidae) for the province - Rossi Rotondi, Enzo Ángel (2020)
A short list of small mammals is provided, from bones found in pellets of the American barn owl (Tyto furcata) collected in four localities in the Arid Chaco of Córdoba province, central Argentina. We identified seven species and one genus belonging to two orders (Didelphimorphia and Rodentia) and four families (Didelphidae, Cricetidae, Ctenomyidae and Caviidae). We also present the first records of Microcavia jayat Teta, Ojeda, Lucero & D’Elia, 2017 for Córdoba province.